VALUE DRIVERS OF BANK EQUITY MARKET PRICE - Gounder, Chitra; Nair, Jyoti (Indian Journal of Finance and Banking, 2023)
The Indian banking sector has shown robustness and resilience in the face of challenges on account of rising non-performing assets and economic upheavals. The market value of bank equity is a reflection of the financial performance of banks and macroeconomic factors. 22 bank-specific variables and 5 macroeconomic factors representing profit management, capital management, shareholder value management and risk and leverage management, India’s Real GDP Growth Rates (Factor Cost), Money Supply growth, Bank Credit growth, Deposit growth rate and Inflation are used in this study. 19440 observations are examined from the financial data of 40 commercial banks (private and public sector banks for a period of eighteen years. The data is analyzed using panel regression. Hausman and Pagan’s test was conducted to find the best-fit model. The results show that Finance Charge Coverage (FCCR), Advance Loan funds, Current Ratio, Beta and Asset Turnover have a negative impact on bank equity value and Activity Mix, Revenue Efficiency, Earnings Retention, and Cost Management shows a positive significant relationship with equity value. Factors like FCCR affects the market values of public sector banks and private sector banks differently Growth in GDP, Inflation shows a positive relationship with the market value of bank equity. Growth in Money Supply has a differential impact on the market value of private sector banks and public sector banks. The results provide useful insights to understand the determinants of the market value of bank equity. It can help bankers frame strategies to maintain and enhance the market value of their equity. JEL Classification Codes: E52, E58, M41.